Software Piracy in the Video Game Market - Oliver Gürtler (University of Bonn, Bonn Graduate School of Economics (BGSE), 2006)
In this paper, the market for video games is considered, where some firms produce both, hardware and software. It is analyzed, whether these firms are interested in strategically enabling software piracy. It will be shown that this is indeed the case, if firms dier substantially in hardware production costs. Then, the low-cost producer gains from enabling software piracy in two ways. First, it increases its market share in the hardware and, accordingly, in the software market. Second, it can raise its hardware price. These two benefits overcompensate the loss resulting from a higher fraction of pirating consumers in the software market.
Keywords: L86; L13; D21; 330; Video Games Market; Software Piracy; Fundamental Transformation